Distance & engagement : walking, thinking and making landscape, Vogt Landscape Architects - Foxley, Alice (Baden : Lars Müller Publications ; [London : Prestel Publishing Ltd.], 2010)
Between search and research / Gunther Vogt -- Introduction : the way we work -- Yorkshire Dales geology -- We are geomorphic agents! -- Novartis campus green -- Novartis campus park -- To the Rhine -- French fortifications -- Glossary -- Geometries of illusion -- London Tate modern -- Workshop -- Echospace -- Bremen European harbour -- The shape of a walk -- Hadspen house estate -- London Parliament square -- Bibliography -- Last word --
boek
Keywords: Vogt Landscape Arrchitects